ANALISIS PENGARUH DPK, CAR, DAN BOPO TERHADAP PROFITABILITAS BANK PANIN DUBAI SYARIAH PERIODE 2015-2020 - Nurul A’la; Isra Maulina; Siti Najma (J-ISCAN: Journal of Islamic Accounting Research, 2022)
This Study was conducted to examine the aims to determine the effect of TPF, CAR and BOPO on profitability Bank Panin Dubai Islamic 2015-2020. The population in this study banks sharia in Indonesia for the period 2015-2020. There are four variables in this study namely third party funds, capital adequacy ratio, operational costs on operational income and profitability. For the dependent variabel (Y) of the study is profitability. The independent variabel (X) in this study includes: third party funds(X1), Capital Adequacy Ratio (X2) and Operational Costs on Operational Income (X3). The research method used is quantitative methods. The results showed that partially the TPF variable had a no effect on profability (ROA), with tcount < ttable (-0,425< 2,120, with significant level of 0,691> 0,05. CAR variable had a positive and significant effect on profability (ROA), with tcount > ttable 2,903>2,120, with significance level of 0,003> 0,05. BOPO variable had a negative and significant effect on profability (ROA) , with tcount> ttable -3,263>2,210, with significance level of 0,005< 0,05. And simultaneously the variables TPF, CAR and BOPO have a effect an Profitability (ROA), with Fcount > Ftable 6,182 >3,20 and significant level of 0,005< 0,05 in Banks Panin Dubai Islamics for the period 2015-2020.